Branding Semiotics, tips to Innovate in SMEs in Colombia - Barón Pulido, Mireya; Lotero Echeverri, Gabriel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
The mass media and multitasking (Piscitelli, 2009) society requires from the manager to consider the relationship and impact of what his brand communicates. The design of online communicative strategies and their link to consultancy models (Pfefferman, 2011) – where the manager himself becomes the entrepreneur of his own organization — becomes the strength of the branding communication of the organization (Capriotti, P., 2009). The paper exposes the research findings obtained from the study done with small and medium enterprisess (SMEs) in Medellin and Bogotá (Colombia). This qualitative research examines the organizations capabilities toward the appropriation of opportunities on behalf of digital communication. Finally it makes a consultancy proposal addressed to pymes entrepreneurs from the perspective which considers the “Enterprise as a sign and as a semiosis”. It is claimed that if something is not communicated it will not generate any reminder at the level of the client. The results research -which compiles Medellin and Bogotá data- are published upon two products: A book to the organizational communication field, and a multimedia guide to business owners. It is a qualitative studio but with a quantitative phase, applying survey forms.